Stable Seasonal and Annual Alpha Diversity of Benthic Diatom Communities Despite Changing Community Composition - Virta, Leena; Soininen, Janne; Norkko, Alf (Frontiers in Marine Science, 2020)
The global biodiversity loss has raised interest in the different facets of diversity, and the importance of diversity for ecosystem functions has been recognized. However, our knowledge on seasonal and inter-annual variation in the composition and diversity of communities is still poor. Here, we investigated the seasonal and inter-annual changes in taxonomic and functional community composition and diversity of benthic diatoms in a coastal habitat of the northern Baltic Sea, where seasonal and inter-annual variation of climate is pronounced. We found that the taxonomic and functional alpha diversity remained stable at seasonal and inter-annual level despite strong changes in community composition. However, alpha diversity decreased during an exceptionally warm winter possibly due to disturbances induced by the lack of ice. This may suggest that climate warming and consequently limited ice cover will affect the diversity of benthic communities.